2020
DOI: 10.1111/ele.13480
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus alleviation of nitrogen‐suppressed methane sink in global grasslands

Abstract: Grassland ecosystems account for more than 10% of the global CH 4 sink in soils. A 4-year field experiment found that addition of P alone did not affect CH 4 uptake and experimental addition of N alone significantly suppressed CH 4 uptake, whereas concurrent N and P additions suppressed CH 4 uptake to a lesser degree. A meta-analysis including 382 data points in global grasslands corroborated these findings. Global extrapolation with an empirical modelling approach estimated that contemporary N addition suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Approximately 50% of the in situ, on-site GHG flux data (i.e., NEE, CH4 or N2O) were seasonally measured, e.g., covering the growing season (temperate and boreal peatlands) or the wet season in (sub)tropical peatlands (Table 2). Therefore, to calculate the annual fluxes for these studies, we applied a previously used gap-filling approach 58,59 . Specifically, the annual NEE, CH4 or N2O (kg CO2/ CH4/ N2O ha -1 yr -1 )…”
Section: Global-scale Changes In the Net Ghg Balance Due To Drainagementioning
confidence: 99%
“…Approximately 50% of the in situ, on-site GHG flux data (i.e., NEE, CH4 or N2O) were seasonally measured, e.g., covering the growing season (temperate and boreal peatlands) or the wet season in (sub)tropical peatlands (Table 2). Therefore, to calculate the annual fluxes for these studies, we applied a previously used gap-filling approach 58,59 . Specifically, the annual NEE, CH4 or N2O (kg CO2/ CH4/ N2O ha -1 yr -1 )…”
Section: Global-scale Changes In the Net Ghg Balance Due To Drainagementioning
confidence: 99%
“…Beside the increased substrate availability for methanogenesis, eCO 2 may stimulate microbial activities for CH 4 production (Conrad, 2002) and inhibit CH 4 oxidation (Bodelier & Laanbroek, 2004;Ineson et al, 1998) by reducing soil N availability that may partially release the N suppression on methanotrophs (Xu et al, 2004;Zhang et al, 2020). The simulated stimulating impacts of eCO 2 on CH 4 emission is partially due to greater aerenchyma in plant tissues that promotes CH 4 transport (Bellisario et al, 1999;Megonigal & Schlesinger, 1997).…”
Section: Different Mechanisms Of Warming and Eco 2 Impacts On Ch 4 Cyclingmentioning
confidence: 99%
“…Many in situ measurements and in vitro experiments found that N addition could suppress CH 4 uptake in upland soil (Bodelier & Laanbroek, 2004; King & Schnell, 1994; L. Zhang et al., 2020). In a meta‐analysis by Liu and Greaver (2009), CH 4 uptake decreased by 38% across all ecosystems under N addition.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the global soil CH 4 sink was predicted to be enhanced during the 21st century with warming scenarios, but nitrogen (N) deposition could reduce the future sink (Zhuang et al, 2013). In the context of increased global nitrogen deposition, the effects of N deposition on soil CH 4 sinks and the associated mechanisms are receiving increasing attention.Many in situ measurements and in vitro experiments found that N addition could suppress CH 4 uptake in upland soil (Bodelier & Laanbroek, 2004;King & Schnell, 1994;L. Zhang et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation